2020
DOI: 10.1063/5.0004513
|View full text |Cite
|
Sign up to set email alerts
|

Van Gurp–Palmen relations for long-chain branching from general rigid bead-rod theory

Abstract: This report is circulated to persons believed to have an active interest in the subject matter; it is intended to furnish rapid communication and to stimulate comment, including corrections of possible errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…3(d)) as a gradual increase in d as G* decreases with increasing x PPnBA . 26,27 The fact that PnBA and PPnBA elastomers have different relaxation modes motivated us to gain further insights into the thermodynamics of these dynamic polymer interactions, which are predicted to be key to the use of BBPs for self-healing and processable materials.…”
Section: Resultsmentioning
confidence: 99%
“…3(d)) as a gradual increase in d as G* decreases with increasing x PPnBA . 26,27 The fact that PnBA and PPnBA elastomers have different relaxation modes motivated us to gain further insights into the thermodynamics of these dynamic polymer interactions, which are predicted to be key to the use of BBPs for self-healing and processable materials.…”
Section: Resultsmentioning
confidence: 99%
“…The selfsimilarity of the dynamic moduli curves at different temperatures and the van Gurp−Palmen plot suggest that universal curves can be constructed by applying the TTS principle. 9,20 To do so, vertical shift factors b T (b T = ρ 0 T 0 /ρT), where T 0 is set to 300 K and ρ 0 is the density of SBR at the reference temperature (300 K), were utilized to calculate the rescaled moduli, i.e., b T G′ and b T G″. Similar to the experiments, the horizontal shift factors a T were determined manually by fixing moduli data at the reference temperature and sliding the other curves on the horizontal axis to obtain a continuous curve.…”
Section: Chain Mobilitymentioning
confidence: 88%
“…Multiple studies have reported the success of TTS in extending the timescale of rheological measurements for a variety of complex fluids, including linear and branched polymers, cross-linked networks, elastomers, , coordination polymers, , biopolymers, and asphalts. , In the case of blends and some copolymers, the polymer sample can show multiple glass transition temperatures, which can be described by Lodge and McLeish model . It is important to note that these studies show the applicability of TTS over the frequency range accessible in commercially available rheometers (3 to 4 orders of magnitude).…”
Section: Introductionmentioning
confidence: 92%
“…Hassager derives the expression for the shear relaxation function from general rigid bead-rod theory for axisymmetric macromolecules, 17,18 G(s) ≡ (2η s + nζL…”
Section: Fig 2 [(A)-(c)]mentioning
confidence: 99%
“…( 3) to study the effect of architecture on Möbius macromolecules. Since general rigid bead-rod theory relies entirely on macromolecular orientation for explaining rheological responses of macromolecular suspensions, 17 the theory neglects interactions between macromolecules. We are attracted to general rigid beadrod theory for the accuracy of its predictions for its simplest special cases and to the rigid dumbbell, at least qualitatively, for most of the viscoelastic material functions measured in the laboratory (see Introduction of Refs.…”
Section: Introductionmentioning
confidence: 99%